A CRITICAL REVIEW ON MEDOHARA (ANTIDYSLIPIDAEMIC) ACTION OF STEM BARK OF CIRABILWA (HOLOPTELEA INTEGRIFOLIA PLANCH.) WITH SPECIAL REFERENCE TO AYURVEDIC AND MODERN ASPECT (International Journal of Ayurveda and Pharma Research, 2018)
Dyslipidaemia (Medovikara) is a major health problem in both developed and developing nations. It leads to Atherosclerosis, which is a major factor in the development of Cardiovascular diseases. Modern medications available to Dyslipidaemia are potentially hazardous. Cirabilwa (Holoptelea integrifolia Planch.) is a large deciduous tree distributed throughout the greater part of India upto an altitude of 2000 ft. It is used in the treatment of various diseases including Dyspepsia, Flatulence, Colic, Helminthiasis, Vomiting, Skin diseases, Diabetes Mellitus, Haemorrhoids and Rheumatism. It is included in many Medohara ganas (groups of drugs having anti dyslipidaemic action) like Lekhana mahakashaya group (group of drugs that dessicate and scrape away the morbid tissues especially Meda and Kapha) of Caraka Samhita; Shleshma samsamana (groups of drugs which decrease Kapha), several Kaphamedohara groups (groups of drugs which decrease Meda and Kapha) like Saalasaradi, Varanadi, Aragwadadi, Asanadi and Arkadi of Susruta Samhita; Asanadi, Varanadi, Aragwadadi and Arkadi groups of Ashtanga Hridaya. This is an attempt made to explain the Medohara action of Cirabilwa according to Ayurvedic as well as modern aspect.